Hubungan Pelanggaran Kontrak Psikologis dan Kepribadian Tipe A dengan Intensi Turnover Karyawan Bank - Ramadhany, Ni Putu Ayu Saraswati; Simarmata, Nicholas (Jurnal Psikologi Udayana, 2014)
One of the common phenomena in organization is the failure in fulfilling promise in retention management, which leads to psychological contract violation and triggers turnover intention. Other phenomenon is difference of employees personality. Employees with type A personality have characteristics which make them tend to react negatively and have high turnover intention. Analogously with Wattson Wyatt survey (2007) that found turnover level among bank employees reached 6,3%-7,5% which was high compared to other industries, it becomes important to study turnover intention among bank employees. According to that, researcher wants to find relationship between psychological contract violation and type A personality on turnover intention of bank employees, simultaneously and individually.   Subjects in this research are 52 employees of bank X in Denpasar. Method used in this research is correlational study. Data are collected by questionnaire. Turnover intention questionnaire has 23 valid items and its reliability coefficient is 0,896. Psychological contract violation questionnaire has 18 valid items and its reliability coefficient is 0,870. Type A personality questionnaire has 35 valid items and its reliability coefficient is 0,965. Data are normal and linear. Multiple regression and partial correlation are run for data analysis. The result of this research finds positive significant relationship between psychological contract violation and type A personality on turnover intention. The reliability coefficient is +0,863. The value of coefficient of determination is 0,744, which shows psychological contract violation and type A personality has 74,4% contribution to turnover intention.  Type A personality has positive significant relationship with turnover intention. The reliability coefficient is 0,556. There is no relationship between psychological contract violation and turnover intention.   Keywords: turnover intention, psychological contract violation, type A personality, bank employees